Does Cervical Plate Add Value in Single or Double Level Anterior Cervical Discectomy and Fusion? - Tariq Elemam (Egyptian Spine Association, 2018)
Background Data: Optimal surgical approach for anterior cervical discectomy and fusion (ACDF) is still controversial. Some authors believe that addition of locking plate (ACDFP) has higher costs and longer operative time. Other surgeons believe that ACDFP have better clinical outcomes and more sound fusion. The debate is higher in single and double level ACDF. Purpose: To compare the clinical and radiological outcomes in patients with single or double level cervical disc herniation operated by ACDF versus those operated by ACDFP. Study Design: A retrospective, descriptive controlled, non-randomized, clinical case study. Patients and Methods: Forty patients underwent ACDF. They were divided into two groups; ACDF group and ACDFP fixation group. Each group included 20 patients. They were operated between 2010 and 2017. Participants were evaluated pre-operatively and post-operatively 1, 3, 6, 9 and 12 months after surgery. Operative time, hospital stay and complications were assessed. Pain was scored by a VAS for both upper arm and cervical pain. The clinical outcomes were compared using Odom’s criteria. Cervical fusion was assessed radiologically. Results: The demographic data of the two groups of patients were fairly homogeneous and comparable. ACDFP group showed slightly better clinical outcome parameters in comparison to ACDF group including VAS for cervical pain (9±5 versus 28±11) and Odom’s criteria scores (15 excellent outcome versus 10). Also ACDFP group showed slightly better radiological fusion rate (100%) in comparison to (85%) in ACDF group. Reported nonunion was higher in ACDF group (15%) in comparison to ACDFP group (0%). Conclusion: Our data suggest that the addition of cervical plate fixation to ACDF might leads to better clinical outcome and radiological fusion in single and double cervical disc disease. (2018ESJ155)